Pelaksanaan Penanggulangan Perjudian dan Sanksi Berdasarkan Peraturan Nagari Sungai Kamuyang Nomor 07 Tahun 2003 tentang Penyakit Masyarakat (Pekat) - Utami, Cici; Fitriani, Hellen Last; Nurhadi, Nurhadi (ANWARUL, 2022)
Gambling is very rampant in the Kamuyang Sungai Nagari, although there are already rules that regulate it, which is stated in the Kamuyang Sungai Nagari Regulation No. 07 of 2003 concerning Community Diseases. This gambling does not recognize age, ranging from children to adults doing gambling practices and does not recognize gender. They think that by gambling it is easy to earn money without having to work hard. The method used here is the sociological method, namely research conducted based on the understanding and interpretation of an event in the reciprocal relationship between law and social phenomena by identifying the law and how this law applies in society, gambling here is very difficult to eradicate because of the ineffectiveness of the regulations. has been created and published. even those who practice this gambling from among those who make rules regarding this gambling ban. The inhibiting factor in the implementation of overcoming gambling in Sungai Kamuyang Nagari is due to the ambiguity of the Nagari government in implementing the existing rules, where the government should implement the rules even those who participate in playing the gambling. As well as the lack of public awareness in implementing the applicable legal rules.